2016
DOI: 10.3389/fncel.2016.00152
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Form of Compensation in the Tg2576 Amyloid Mouse Model of Alzheimer’s Disease

Abstract: One century after its first description, pathology of Alzheimer’s disease (AD) is still poorly understood. Amyloid-related dendritic atrophy and membrane alterations of susceptible brain neurons in AD, and in animal models of AD are widely recognized. However, little effort has been made to study the potential effects of combined morphological and membrane alterations on signal transfer and synaptic integration in neurons that build up affected neural networks in AD. In this study spatial reconstructions and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 96 publications
1
10
2
Order By: Relevance
“…This earlier and our recent analyses suggest the two key proteins to affect layer III neocortical pyramidal neurons remarkably differently, leaving synaptic input pattern recognition unaltered in both cases. It was found that Aβ decreases membrane resistance and increases membrane capacitance (Somogyi et al, 2016), whereas in our current article, we report mutant tau protein not to change membrane resistance and capacitance in TG neurons. Aβ was shown to affect the morphology and membrane properties of pyramidal neurons in a way that morphological and membrane alterations compensate each other's pathological effects and subthreshold dendritic signaling, and the input pattern recognition/discrimination remains virtually unaltered (Somogyi et al, 2016).…”
Section: Significance Of Subthreshold Membrane Modelscontrasting
confidence: 81%
See 3 more Smart Citations
“…This earlier and our recent analyses suggest the two key proteins to affect layer III neocortical pyramidal neurons remarkably differently, leaving synaptic input pattern recognition unaltered in both cases. It was found that Aβ decreases membrane resistance and increases membrane capacitance (Somogyi et al, 2016), whereas in our current article, we report mutant tau protein not to change membrane resistance and capacitance in TG neurons. Aβ was shown to affect the morphology and membrane properties of pyramidal neurons in a way that morphological and membrane alterations compensate each other's pathological effects and subthreshold dendritic signaling, and the input pattern recognition/discrimination remains virtually unaltered (Somogyi et al, 2016).…”
Section: Significance Of Subthreshold Membrane Modelscontrasting
confidence: 81%
“…It was found that Aβ decreases membrane resistance and increases membrane capacitance (Somogyi et al, 2016), whereas in our current article, we report mutant tau protein not to change membrane resistance and capacitance in TG neurons. Aβ was shown to affect the morphology and membrane properties of pyramidal neurons in a way that morphological and membrane alterations compensate each other's pathological effects and subthreshold dendritic signaling, and the input pattern recognition/discrimination remains virtually unaltered (Somogyi et al, 2016). Such a compensation of dendritic atrophy by parallel alterations in membrane properties is not possible in rTg4510 mice because of the unaltered nature of passive membrane properties.…”
Section: Significance Of Subthreshold Membrane Modelscontrasting
confidence: 81%
See 2 more Smart Citations
“…There are several methods to group or classify similar data by using the characteristics of the data, such as discriminant analysis (DA) (Kennedy, Kaiser, Fisher, et al, 1980;Klecka, 1980;Lachenbruch & GOLDSTEIN, 1979;Teknomo, 2019), analysis of variation (ANOVA) (Ståhle & Wold, 1989), cluster analysis (Romesburg, 2004;Somogyi, Katonai, Alpár, & Wolf, 2016), and fractal analysis (Smith Jr., Marks, Lange, Sheriff Jr., & Neale, 1989). Multivariate DA is a statistical tool that is widely used in statistics to characterize two or more groups of objects by evaluating linear combinations of group features which affect classification.…”
Section: Theory Of Multivariate Discriminant Analysismentioning
confidence: 99%